An investigation into thyroid function tests in pregnant women and the relationship between thyroid autoantibodies and preeclampsia (Annals of Medical Research, 2021)
Aim: Preeclampsia and eclampsia which can be seen during the last trimester of pregnancy prove to be significant pregnancy complications whose physiopathology still remains unclear. Available data demonstrate that disorders of the thyroid hormone may possibly alter the progress of pregnancy. The aim of this study was to investigate the relationship between thyroid antibodies and preeclampsia development.Materials and Methods: This retrospective study is a total of 216 cases were included in the study out of which 72 were pregnant women with preeclampsia who had been followed-up at University of Medical Sciences, Adana City Hospital, Obstetrics and Gynecology Clinic, 72 were healthy pregnant women followed-up at the same clinic, and 72 healthy non-pregnant women but had presented to the internal medicine clinic for various reasons. Statistical analyses of the comparisons of the thyroid tests and thyroid autoantibodies among the all three groups were conducted as well.Results: 45 of the patients with preeclampsia had mild preeclampsia, while 27 had severe preeclampsia. While no significant difference was found among pregnant women with preeclampsia, healthy pregnant women, and the control groups with regards to the Thyroid Stimulating Hormone (TSH) values as revealed by intergroup and intragroup comparisons for multiple groups, the free triiyodotironin(fT3) and free tetraiyodotironin (fT4) values were found to be significantly lower in the preeclampsia and healthy pregnant groups at an advanced level than the control group statistically (p 0.005). Conclusion: The results of our study revealed that the alterations seen in thyroid hormones might pose a risk for preeclampsia development but autoantibodies were not sufficient enough to bring about preeclampsia development.
Keywords: Hypertension; preeclampsia; pregnancy; thyroid autoantibody